OPTIMIZATION OF VILLAGE WEBSITE AS AN IMPLEMENTATION OF SMART GOVERNANCE IN SMART VILLAGE IN LAWEYAN VILLAGE - Muhammad Sultan Wachid Monda Maulana; Diky Wahyu; Rizky Nizar Wahyu Illahi; Susi Hardjati (JPASDEV : Journal of Public Administration and Sociology of Development, 2023)
Villages are the spearhead of government development. An innovative step in village development is carried out by implementing a smart village concept. This research aims to analyze and describe the optimization of the village website as an application of a smart village in Laweyan Village, Probolinggo Regency. The research approach used a qualitative descriptive method. Data were collected through interviews with informants selected by purposive sampling, field observations, and documentation. The results of this study are 1) the objectives of optimizing the Laweyan Village website include maximizing the dissemination of public information by minimizing costs and effort; 2) the satisfaction alternative shows that the use of the website as a medium for delivering information by the Laweyan Village government has a positive impact in improving the quality of public services and the efficiency of the governance process; 3) the resource indicator that becomes a limitation shows that there are limited human, financial, and infrastructure resources in managing the Laweyan Village website Financial resources are also a limiting factor due to budget priorities for needs that are considered more important by the Village Government. In addition, infrastructure limitations, such as adequate equipment and community understanding of technology, are obstacles to optimizing online services. In general, the Laweyan Village website has made a positive contribution to the dissemination of public information. However, some obstacles still need to be overcome, especially related to human resources, finance, and infrastructure limitations.